Musculoskeletal manifestations of sarcoidosis: perspective of a rheumatologist - V. M. Sidzenka; A. V. Polyanskaya; S. V. Khidchenko; V. G. Apanasovich (Military Medicine, 2026)
Sarcoidosis is a systemic inflammatory disease which clinical manifestations mimic the signs of other pathologies. The authors of the article provide the analysis of musculoskeletal manifestations of sarcoidosis from the perspective of a rheumatologist. Signs from the musculoskeletal system, characteristic of sarcoidosis and rheumatic diseases, are arthropathy, myopathy and bone involvement. Special attention is paid by authors to the possibility of combining sarcoidosis and rheumatic diseases in the same patient. Difficulties of diagnosing are associated with ambiguity of the results of clinical examination, laboratory tests and instrumental studies. Biopsy plays an important role in the diagnosis of sarcoidosis. The article presents distinctive clinical, laboratory and histological signs of the rheumatic diseases in comparison with sarcoidosis. Immunological markers of systemic connective tissue diseases are very helpful for establishing the diagnosis. The article outlines the principles of differential diagnosis of sarcoidosis and rheumatoid arthritis, axial spondyloarthritis, psoriatic arthritis, ANCA-associated vasculitis, systemic lupus erythematosus, systemic sclerosis, primary Sjogren’s syndrome, IgG4-associated disease and inflammatory myopathies. The authors substantiate the importance of using a multidisciplinary approach to diagnosis and raising doctors’ awareness of the clinical manifestations of sarcoidosis and rheumatic diseases.